The 2008 survey of consumer payment choice - Kevin Foster; Erik Meijer; Scott Schuh; Michael A. Zabek (Federal Reserve Bank of Boston, 2010)
This paper presents the 2008 version of the Survey of Consumer Payment Choice (SCPC), a nationally representative survey developed by the Consumer Payments Research Center of the Federal Reserve Bank of Boston and implemented by the RAND Corporation with its American Life Panel. The survey fills a gap in knowledge about the role of consumers in the transformation of payments from paper to electronic by providing a broad-based assessment of U.S. consumers' adoption and use of nine payment instruments, including cash. The average consumer has 5.1 of the nine instruments, and uses 4.2 in a typical month. Consumers make 53 percent of their monthly payments with a payment card (credit, debit, and prepaid). More consumers now have debit cards than credit cards, and consumers use debit cards more often than cash, credit cards, or checks individually. Cash, checks, and other paper instruments are still popular and account for 37 percent of consumer payments. Most consumers have used newer electronic payments, such as online banking bill payment, but they only account for 10 percent of consumer payments. Security and ease of use are the characteristics of payment instruments that consumers rate as the most important.
Keywords: D12; D14; E42; 330